• MICROBIAL CONTAMINATION OF PHARMACEUTICAL PRODUCTS IN A TROPICAL ENVIRONMENT (Biological Sciences - PJSIR, 2002)
Tablets, both coated and non-coated were examined for the microbiological contamination, growth  and  survival. Bacteria  such as KlebsieUa aerogenes, Bacillus cereus, Pseudomonas  aeruginosa,  and  Staphylococcus  aureus  were  dominated  in all the samples screened. Fungi isolated were Penicillium chrysogenum, Aspergillus jlavus and some yeasts as Candida albicans and Saccharomyces spp. Total bacterial counts ranged from 2.0 x 103 to 8 x 107 colony forming units (CFU) per millilitre while mould units ranged from O .2 x  102 to  1.4 x  102  cfu/ml. The bacterial  isolates were further found  to be able to grow and  utilize  the drugs (tablets)  as  sole carbon  and  energy  sources.